Dietary predictors of urinary biomarkers of pyrethroids in the general population: A scoping review - Koyratty, Nadia; Olson, James R.; Kawyn, Marissa; Curl, Cynthia L.; Kordas, Katarzyna (Elsevier, 2023)
Background Pyrethroid pesticides are ubiquitous environmental contaminants, contributing to chronic and potentially harmful exposure among the general population. Although studies have measured pesticide residues on agricultural products, the link between food intake and concentrations of pyrethroid biomarkers in urine remains unclear.